EFEKTIVITAS PROGRAM ADMINISTRASI KEPENDUDUKAN DAFTAR SENDIRI CETAK SENDIRI (AKU DICARI) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BADUNG - Pratiwi, Kadek Mas Febby; Prabawati, Ni Putu Anik; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2022)
Registration Population Administration Program (AKU DICARI) is a program issued by the Department of Population and Civil Registration of Badung Regency. The purpose of the program is to provide convenience and bring services closer to the community. This study uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. The results of this study were analyzed using the effectiveness theory proposed by Duncan which consists of 3 factors, namely the achievement of goals, integration and adaptation, then shows that the implementation of the AKU DICARI Program has not been fully effective because there are still several problems in the indicators, namely the absence of the AKU DICARI Program SOP, there is a daily quota limit for submitting applications, file collection is still being done at the office, socialization is not optimal, lack of supporting facilities and infrastructure and inadequate skills possessed by human resources. Keywords : Effectiveness, AKU DICARI Program